Utilization of Prickly Pear Peels as Agricultural Waste for the Removal of Organic Pollutant from Aqueous Solution - Ageuib Mouna; Ageuib Mouna; Tamer ferial (University of Shahid Hama Lakhdar - El Oued, 2024)
Nowadays, ecosystems still suffer from the dire reflections of dye pollutants. In this study, an ecofriendly and zero-cost was prepared using raw prickly pear peel. The surface and physicochemical properties of PPP-Raw were evaluated by BET, SEM-EDX, FTIR, and pHpzc analyses. Surface analysis revealed that PPP-Raw possesses an enriched composition of nucleophilic functional groups, including OH, NH, and COOH in an alkane medium, leading to diversity in the adsorption mechanism, involving electrostatic attraction, hydrogen bonding, and π − π interactions. This diversity significantly contributed to reaching a maximum adsorption capacity for MV 2B of 569.6 mg/g. The change in thermodynamic state functions ΔG, ΔH, and ΔS suggest the possibility of physisorption simultaneously and indicate the exothermic and spontaneous characters of the adsorption of MV 2B dye on PPP-Raw with negative values of ΔH and ΔG. The findings of this research will further urge the current management of the water environment to embrace the use of raw prickly pear peels as a natural resource adsorbent without any chemical treatments in the remediation of organic dye-contaminated wastewater. في الوقت الحاضر، لا تزال النظم البيئية تعاني من الانعكاسات الرهيبة للملوثات الصبغية. في هذه الدراسة، تم تحضير منتج PPP-Raw صديق للبيئة وبدون تكلفة باستخدام قشر التين الشوكي الخام. تم تقييم الخصائص السطحية والفيزيائية والكيميائية ل يمتلك تركيبة غنية من PPP-Raw كشف التحليل السطحي أن .pHpzc و FTIR ، SEM-EDX ، BET بواسطة تحليلات في وسط ألكاني، مما يؤدي إلى التنوع في آلية الامتزاز، COOH و NH ،OH المجموعات الوظيفية المحبة للنواة، بما في ذلك وقد ساهم هذا التنوع بشكل كبير في الوصول إلى .π - π بما في ذلك الجذب الكهروستاتيكي والترابط الهيدروجيني وتفاعلات ΔS و ΔH ، ΔG تبلغ 569.6 ملغم/غم. يشير التغير في وظائف الحالة الديناميكية الحرارية MV 2B أقصى قدرة امتصاصية ل MV 2B إلى إمكانية الامتصاص الفيزيائي في وقت واحد ويشير إلى الخصائص الطاردة للحرارة والعفوية لامتصاص صبغة ستحث نتائج هذا البحث الإدارة الحالية للبيئة المائية على تبني استخدام قشور التين .ΔG و ΔH مع قيم سالبة ل PPP-Raw على الشوكي الخام كمورد طبيعي ممتز دون أي معالجات كيميائية في معالجة مياه الصرف الصحي الملوثة بالصبغة العضوية.
Master's theses in chemical engineering
Keywords: Adsorption; Response surface methodology; Prickly pear peel; MV 2B dye.; .MV 2B الامتزاز، منهجية سطح الاستجابة، قشر التين الشوكي، صبغة .